Оцифрування інформації, як пріоритетний напрямок збереження бібліотечних фондів - Ярка, Уляна; Мина, Жанна (Видавництво «Редакція «УП», 2016)
This article raises current questions digitization of information from library. Their importance to preserve material for future generations, protection against fires, destruction and war. The possibility of a second life to damaged and destroyed objects over time. The perspective of universal access to rare copies. And it considers important stages of selection, the legality of the transfer of data in digital format and their publication, copyright works. Also, the article presenting the latest advanced services of storage of electronic data.
Keywords: оцифровування; цифрова копія; цифровий аналог; збереження; віртуальні бібліотеки; культурна спадщина